Structures and Optical Properties of Anodic Aluminum Oxide Thin Films - Fan, Qi Hua; Galipeau, David; Ghimire, Baibhav; Gupta, Rakesh Kumar; Dubey, Mukul; Mandal, Nitu (Journal of Coating Science and Technology, 2014)
Low refractive index materials (n<1.3) are not common in nature. However, they are essential for antireflection coatings. In this study porous anodic aluminum oxide (AAO) on glass substrate was fabricated by electrochemical oxidation and subsequent etching. The pore size was modulated from less than 80 nm to more than 250 nm. The pore depth was controlled by electrochemical anodization and/or chemical etching time. It is challenging to effectively quantify the pore structures and the optical properties of such porous materials. Using spectroscopic ellipsometry, the authors showed that the AAO materials had tunable refractive index from 1.25 to 1.40, which is ideal for antireflection coating on glass (n=1.54). In addition, quantitative information on the AAO film porosity, profile structure, film thickness, dielectric constants, and roughness was also derived from the ellipsometry analysis. It was shown that the as-fabricated AAO film included trace amount of residual metal aluminum with an effective thickness ~0.28 nm.